Ramrod [videorecording (DVD)] - De Toth, André, 1912-2002; McCrea, Joel, 1905-1990; Lake, Veronica; Defore, Don, 1913-1993 (Olive Films, 2012)
Connie Dickason has inherited a sheep ranch from her ex-husband and is determined to run the ranch with the help of her new Ramrod and his crew of locals despite the opposition of Ivey and her father. The resulting bloody range war is much to the dismay of Dave, who wants to resolve Connie's problems with Ivey legally.